The patterns of exercise-induced β-endorphin expression in the central nervous system of rats. (August 2020) - Xue, Liang; Sun, Jinrui; Zhu, Jiandi; Ding, Yi; Chen, Shuhuai; Ding, Mingxing; Pei, Hong
Abstract: Exercise at different intensities is able to induce different physical and psychological statuses of the subjects. The β-endorphin (β-EP) in central nervous system is thought to play an important role in physical exercise. However, its expression patterns and physiological effects in the central nuclei under different exercise states are not well understood. Five-week old male Sprague-Dawley rats were randomly divided into two groups of 21 each: Control and Exercise. Control rats were sedentary while Exercise rats were arranged to run on a treadmill (5-week adapting or moderate exercise and 2-week high-intensity exercise). Seven rats were taken from each group at day33, day42 and day49 for examination of blood biochemical parameters (lactate, Lac; blood urea nitrogen, BUN; glucose) and for detection of nuclei β-EP level with immunohistochemistry. The results showed that Lac and BUN levels were significant increased after the high intensity exercise. The five-week exercise caused a significantly increased β-EP in caudate putamen (CPu), amygdala, paraventricular thalamic nucleus (PVT), ventromedial hypothalamus nucleus (VMH) and gigantocellular reticular nucleus (Gi). The high intensity exercise induced an elevated β-EP in CPu and nucleus of the solitary tract (Sol), but a decreased β-EP in globus pallidus (GP). Compared with Control, exercise rats showed an elevated β-EP in CPu, PVT, VMH, accumbens nucleus, Gi and Sol, and a decreased β-EP in GP at day49. The β-EP levels in acurate nucleus, periadueductal gray and parabrachial nucleus were not changed at day33, 42 and 49. In conclusion, β-EP levels in different nuclei changed under the moderate and high intensity exercises, which may contribute to modifying exercise-produced psychological and physiological effects.